AIR POLLUTION MODELING: A CASE STUDY OF THE CEMENT INDUSTRY IN PALIMANAN DISTRICT, CIREBON REGENCY - Abdillah, Hafidz
The development of the cement industry, which tends to be fast in line with Indonesia's economic growth, apart from having a positive impact, also has some negative impacts. One of these negative impacts is the worsening of air quality due to emissions from cement production processes. One of the methods to estimate its impact on air quality is by doing a dispersion modeling. In this study, the AERMOD dispersion model will be used, a model developed by the US EPA. The cement industry used as the object of research is a cement industry in Cirebon Regency. Based on the modeling results, it was found that point source emissions from the related cement industry could cause exceedances of ambient air quality standards for SO2 and NO2 parameters. All incidents exceeding these standards occurred at night when atmospheric conditions tended to be stable. In addition, the dispersion of air pollutants originating from these emissions tends to be concentrated in areas that have hilly contours, especially in areas around mountains or hills.